Metaphors of Longing in the Selected Poems of Aan Mansyur’s There Is No New York Today (2016) - Ely Muliawati (Universitas Pendidikan Indonesia (UPI), 2019)
Metaphor is not merely a matter of language, but it is also concerned with the conceptual system of an individual. There Is No New York Today (2016) by Aan Mansyur is a poetry anthology that employs metaphors to deliver the themes of the poems. This study attempts to investigate how the metaphors work in conveying the theme of longing in the 10 selected poems of Aan Mansyur. The three theories, consisting of Lakoff and Johnson’s (2003) conceptual metaphor theory, Kovecses’s (2010) common target and source domains formula, and Scheibe, Freund, and Baltes’s (2007) longing characteristics, are employed to unravel the types of target and source domains in the metaphors and examine the way the metaphors construe the persona’s state of longing. The findings show there are at least 28 metaphors of longing discovered in this study, wherein 10 target domains and 22 source domains are identified. Based on the analysis of these metaphors, longing becomes the major theme expressed throughout the poems. The persona is found to encounter five longing characteristics, namely feeling of incompleteness, persona utopia, emotional ambivalence, tri-time focus, and reflective and evaluative component. The dominant longing characteristic found in this study is feeling of incompleteness, in which mostly conveyed by the natural forces as the source domain. The variety of metaphors are proven to conveyed the theme of longing differently, as different characteristics appear to show different side of longing encountered by the persona. In this study, the metaphors are proven to take a crucial part in conveying the abstract concept of human feeling, namely longing, as well as enriching the meaning of the longing in the poem into several layers, from the negative state to the positive developmental one. Keywords: conceptual metaphor, longing, poetry, source domains, target domains